Spatiotemporal coastline variations in the Pearl River Estuary and the relationship with multiple human disturbances - Li, Xin; Yan, Haiming; Yang, Ying; Xu, Zhihao; Yang, Huicai (Frontiers in Marine Science, 2022)
Coastlines and estuaries as one of the most dynamic systems in the marine environment are influenced by not only natural factors but also various anthropogenic activities, but there have been limited comprehensive studies on the relationship between coastline variation and anthropogenic activities at the watershed and local scales. The Pearl River Estuary (PRE) in China has experienced remarkable coastline variation along with rapid economic development and urbanization. In this study, the coastline of the PRE was extracted using Landsat images during 1987-2017, and the impacts of multiple factors on coastline variation were explored with correlation analysis and regression analysis. Results suggested coastlines of the PRE demonstrated a clear expanding trend over recent decades, and the coastline length had increased by 74.81 km and the land area had increased by 679.25 km2 by 2017, and results also showed rapid coastline variation during 1987-2004 and relatively slow variation during 2004-2017. Artificial coastlines accounted for 80.90% of the total coastline length in 2017, while natural coastlines accounted for only 19.10%. In addition, reduction in the sand content caused by construction of reservoirs and river dredging in upstream areas played a dominant role in affecting natural coastline variation in the PRE, especially on the west coast. Moreover, the artificial coastline in the study area expanded quickly due to the influence of various human activities, among which the urbanization and land reclamation for aquaculture played a dominant role in affecting the artificial coastline variation on the east and west coasts, respectively. Results of this study have important value for understanding the individual and joint effects of various human activities on coastline variation and can provide important reference information for the sustainable management of the PRE as well as other estuaries.